Right to Freedom From Discrimination: The Case of The Disabled in The Context of International Human Rights and The Practice in Nigeria. - J. Adams Adoga-Ikong; Adaeze Favour Ibekwe (PINISI Discretion Review, 2021)
One of the very issues in the world today that has always been on the front burner is that of human rights.  Nationally and internationally, this issue has been a problem to world leaders.  This is because the way and manner human rights is handled by either the government agencies, institutions and even individuals is such in a sorry state.  The worst is that of the right of the disabled ones among us.  They are inhumanly discriminated against due to their physical or mental state.  They are not given access to certain facilities, employment, education, etc.  In Nigeria as a case study in this research, this has been played out for a long time despite the laws in place to curb this situation.  The disabled are not given equal opportunities to vote, accessing public facilities, equal employment, etc.  This work therefore is an examination of the practice of discrimination against the disabled in Nigeria where they are denied their basic rights on the basis of their condition.  Looking at this situation, it is believed that if in Nigeria, we have to comply with the legislations on ground as well as the various international laws and treaties that Nigeria is a signatory to, the issue of human rights of the disabled will be well practiced.